Religious Freedom in Indonesia: An Islamic Human Right Perspective - Linda Evirianti (UIN Sunan Kalijaga Yogyakarta, 2017)
Everyone has the right of religious freedom or belief which becomes one of important parts of Human Rights (HAM/Hak Asasi Manusia). Thus, no one can be subjected to coercion that can interfere his freedom to adopt or embrace a religion or belief of his choice. The main characteristic of modern constitutional state is the guarantee of human rights in its constitution. In the Constitution NKRI 1945 has set human rights and the rights of citizens in the form of guarantees freedom for each citizen to embrace religion and worship according to their religion or belief. A state guarantees the freedom of each citizen to adopt a religion or belief, but the state (the government) must regulate the freedom in implementing and practicing a religion or belief so that the government can respect, protect, enforce and promote Human Right (HAM) and conserving security, order, health or public morals. Speaking of human rights in Islam is not an historical product arising from human ideology, a concept that has a theological dimension and will be accountable to God. Freedom of thought, conscience, religion and belief is part of the most important human rights, even have status as a right that should not be reduced and violated under any circumstances. On the other hand, religious freedom protects the phenomenon that can be controversial and dangerous for human existence, because religion and systems of ideological belief can be misused to trigger intolerance, discrimination, prejudice, hatred, and violence.[Setiap orang berhak atas kebebasan beragama atau kepercayaan yang menjadi salah satu bagian penting Hak Asasi Manusia. Dengan demikian, tidak ada yang bisa terkena paksaan yang bisa mengganggu kebebasannya untuk mengadopsi atau menganut agama atau kepercayaan pilihannya. Karakteristik utama negara konstitusional modern adalah jaminan hak asasi manusia dalam konstitusinya. Dalam Konstitusi NKRI 1945 telah menetapkan hak asasi manusia dan hak warga negara dalam bentuk jaminan kebebasan bagi setiap warga negara untuk merangkul agama dan ibadah sesuai agama atau kepercayaan mereka. Sebuah negara menjamin kebebasan setiap warga negara untuk mengadopsi agama atau kepercayaan, namun negara (pemerintah) harus mengatur kebebasan dalam melaksanakan dan mempraktikkan agama atau kepercayaan sehingga pemerintah dapat menghormati, melindungi, menerapkan dan mempromosikan Hak Asasi Manusia (HAM). Dan melestarikan keamanan, ketertiban, kesehatan atau moral publik. Berbicara tentang hak asasi manusia dalam Islam bukanlah produk historis yang muncul dari ideologi manusia, sebuah konsep yang memiliki dimensi teologis dan akan bertanggung jawab kepada Tuhan. Kebebasan berpikir, hati nurani, agama dan kepercayaan adalah bagian dari hak asasi manusia yang paling penting, bahkan memiliki status sebagai hak yang tidak boleh dikurangi dan dilanggar dalam kondisi apapun. Di sisi lain, kebebasan beragama melindungi fenomena yang bisa kontroversial dan berbahaya bagi eksistensi manusia, karena agama dan sistem kepercayaan ideologis dapat disalahgunakan untuk memicu intoleransi, diskriminasi, prasangka, kebencian, dan kekerasan.]